The paraspecific neutralisation of snake venom induced coagulopathy by antivenoms - Ainsworth, Stuart (2018)
Snake envenoming causes several potentially lethal pathologies. The specific pathology is dictated by the toxin composition of venom, which varies by species, geography and ontogeny. This variation severely restricts the paraspecific efficacy of antivenoms used to treat snakebite victims. With a view to devising pathology-specific snakebite treatments, we assessed the procoagulant activity of 57 snake venoms and investigated the efficacy of various antivenoms. We find that procoagulant venoms act differentially on key steps of the coagulation cascade, and that certain monospecific antivenoms work in a previously unrecognised paraspecific manner to neutralise this activity, despite conventional assumptions of congener-restricted efficacy. Moreover, we demonstrate that the metal chelator EDTA is also capable of neutralising venom-induced lethality in vivo. This study illustrates the exciting potential of developing new, broad-spectrum, toxin-targeting antivenoms capable of treating key snakebite pathologies and advocates a thorough re-examination of enzyme inhibiting compounds as alternative therapies for treating snakebite victims.